2023
DOI: 10.1177/20563051231157300
|View full text |Cite
|
Sign up to set email alerts
|

A God-Tier LARP? QAnon as Conspiracy Fictioning

Abstract: The QAnon movement, which gained a lot of traction in recent years, defies categorization: is it a conspiracy theory, a new mythology, a social movement, a religious cult, or an alternate reality game? How did the posts of a (supposedly) anonymous government insider named Q on an obscure online imageboard in October 2017 instigate a serious conspiracy movement taking part in the storming of the US Capitol in early 2021? Returning to the origins of QAnon on 4chan’s Politically Incorrect board and its initial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…We articulated three analytically distinct epistemological positions that users of r/conspiracy take: belief (the conflict over true and false), doubt (the conflict over whether anything can be known, preferring instead to doubt all received truths), and play (the conflict over whether that is even the point, preferring to entertain conspiracy theories for the fun of engaging with them). Without wanting to overemphasize the importance of ironic participation—belief and doubt are, still, at least as important to what makes r/conspiracy a participatory conspiracy culture—this latter position of playful participation is theoretically relevant and underexplored; although some authors have recently started to explore it (de Zeeuw and Gekker, 2023). By empirically mapping it, we find an answer to the calls of what several authors cited above have previously identified as a blind spot of conspiracy research.…”
Section: Conclusion: Participatory Conspiracymentioning
confidence: 99%
“…We articulated three analytically distinct epistemological positions that users of r/conspiracy take: belief (the conflict over true and false), doubt (the conflict over whether anything can be known, preferring instead to doubt all received truths), and play (the conflict over whether that is even the point, preferring to entertain conspiracy theories for the fun of engaging with them). Without wanting to overemphasize the importance of ironic participation—belief and doubt are, still, at least as important to what makes r/conspiracy a participatory conspiracy culture—this latter position of playful participation is theoretically relevant and underexplored; although some authors have recently started to explore it (de Zeeuw and Gekker, 2023). By empirically mapping it, we find an answer to the calls of what several authors cited above have previously identified as a blind spot of conspiracy research.…”
Section: Conclusion: Participatory Conspiracymentioning
confidence: 99%
“…This adjustment has found right-wing one-world government conspiracy theorists finding common cause with left-wing anti-vaxxers via their shared antagonism toward figures like Bill Gates and the World Economic Forum. Reformist visions for a more sustainable form of global capitalism, such as the World Economic Forum's Great Reset proposal, are interpreted through this lens as sinister plans for “population control.” But whereas the ritual communication of QAnon arguably had “fictioning” at its core (Zeeuw and Gekker, 2023) to create alternative worlds based around far-fetched fantasies like “Pizzagate,” the Great Reset conspiracy theory is more difficult to untangle from legitimate critiques (Tuters and Willaert, 2022). As the critique of power often resorts to metaphors, efforts to fact-check post-QAnon conspiracy theorizing can backfire because metaphors cannot be fact-checked.…”
Section: Disinformation As Rituals Of Lived Experiencementioning
confidence: 99%
“…The latter term is inspired by Lippmann's (1997Lippmann's ( [1922, p. 20) concept of the 'pseudo-environment' to describe how people construct their own models of reality, summarized in the idea that people 'live in the same world, but [they] think and feel in different ones' . Lippmann was already acutely aware of the growing role of the mass-media in shaping behavior in the real world based on those 'fictions, ' similarly to how QAnon has been shown to use game mechanics and 'fictioning' techniques in their participatory worldbuilding efforts (de Zeeuw and Gekker, 2023). This once more raises the question of how we could 'fit' those practices into existing 'digital public sphere' frameworks, to which I now turn.…”
Section: Introductionmentioning
confidence: 96%